Voluntary versus enforced team effort - Claudia Keser; Claude Montmarquette (Games, 2011)
We present a model where each of two players chooses between remuneration based on either private or team effort. Although at least one of the players has the equilibrium strategy to choose private remuneration, we frequently observe both players to choose team remuneration in a series of laboratory experiments. This allows for high cooperation payoffs but also provides individual free-riding incentives. Due to significant cooperation, we observe that, in team remuneration, participants make higher profits than in private remuneration. We also observe that, when participants are not given the option of private remuneration, they cooperate significantly less.
Keywords: C72; C90; H41; J33; 330; team effort; voluntary collaboration; experimental economics